POPULATION BIOLOGY OF MUD CRAB Scylla serrata - Forsskal, 1775 IN MANGROVE ECOSYSTEM OF SUBANG DISTRICT, WEST JAVA - Ayu Annisa Kumalah; Yusli Wardiatno; Isdradjad Setyobudiandi; Achmad Fahrudin (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
The study of population biology of mud crab Scylla serrata is necessary to analyse the population dynamics, such as growth of crabs, size distribution, mortality and exploitation rates of S. serrata. Population biology data collection was carried out from March to June 2016 at estuary and silvofishery areas of three stations (Mayangan, Tanjung Tiga and Blanakan villages). Data were analyzed using analytical methods of FISAT-II (FAO-ICLARM Stock Assessment Toool II)instruments. The results showed the growth of S. serrata male in Subang distric was positive allometric and the female was negative allometric. Growth coefficient (K) ranged from 0.21 to 0.43 in the estuary and from 0.28 to 0.89 in silvofishery area. Exploitation rate in the silvofishery area has been above the maximum exploitation rate. The size distribution of S. serrata in Subang district has the highest frequency at class interval of 106-110 mm (male) and of 101-105 mm. The highest abundance of mature female crabs is in May.Keywords : population biology, Scylla serrata, Subang District